Decent Work and Green Employment: An Analysis Based on Pluridimensional Character of Sustainability - Oliveira, Flavia de Paiva Medeiros de (2016)
The principle of sustainable development has the purpose of ensure compatibility between the economic development and the preservation of natural resources for presents and futures generations. It´s concretized in everyday life by sustainability, that needs to be broadly considered. The objective of this work is to analyze the green employment and decent work´s programs developed by ILO based on pluridimensional character of sustainability with a view to characterizing as green only the work stations that are, at the same time, sustainables from ambiental and social points of view, considering that this criterion broadly identifies the man with his surround.